Pengembangan Bahasa Ekspresif Anak Melalui Metode Bercerita Gambar Seri di Taman Kanak-Kanak Santa Theresia 1 Pangkalpinang - Imelda Indah Bulan (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This classroom action research aims to develop children's expressive language skills through the serial picture storytelling method at St. Theresia I Pangkalpinang Kindergarten. The method used in this research is classroom action research which is carried out as an effort to overcome problems that arise in the classroom. This method is carried out with three stages, namely planning, implementation, and reflection. The subject of the research was the students of St. Theresia 1 Pangkalpinang Bangka Belitung Kindergarten, totaling 13 children. The object of this research is expressive language skills. The data collection method used was observation. Technical data analysis is done descriptively qualitative. This research was conducted in two cycles. The results showed that from the aspect of assessing children's ability to repeat simple sentences at the beginning of the cycle there were 54% (7 people) who were considered less or not able, but at the end of the cycle after being treated using the serial picture storytelling method, only 8% (1 person) was found who had not been able to repeat simple sentences properly. For the aspect of assessing children's ability to express opinions to others at the beginning of the cycle there were 77% (10 people) who were considered less or not able, but at the end of the cycle only 23% (3 people) of 13 children were found who were not able to express opinions to others. For the aspect of assessing children's ability to retell stories that have been told by the teacher, at the beginning of the cycle there were 69% (9 people) who were considered less or not able, but at the end of the cycle only 15% (2 people) of 13 children who have not been able to retell stories that have been told by the teacher properly. Keywords: expressive language skills, storytelling method, picture series